Water Model Study on Alloy Melting and Mixing in RH Refining Process - XU Zhibo; CHEN Chao; WANG Jia; LI Yihong; CAO Ruiyun; ZHAO Yansong; XUE Liqiang; FAN Jinping (Taiyuan Ligong Daxue xuebao)
[Purposes] At different stages of RH refining process, a large weight of alloys are added to adjust the composition of steel. The motion, melting, and mixing of alloy in RH determine the production rate of refining process. [Methods] The transport process and mixing phenomenon of NaCl saturated solution or NaCl particles in water model of RH were studied by water model experiment and numerical simulation. The salt spheres made by KCl solution were used to simulate the heavy alloy, and the motion and mixing process after entering RH from the top of vacuum chamber in the water model was studied. [Findings] The results show that the dimensionless concentration-time curves of the schemes of particles and solution are consistent at each monitor point. The response time and the first peak time of the particle scheme are slightly later than those of the solution scheme, and the first peak concentration of the partide scheme is also lower. This is due to the dissolution process of particle. When the volume of the solution or the mass of particle increases, the first peak concentration of the scheme of salt solution at the outlet of the down-snorkel is larger and the peak time is shorter. The mixing time of schemes of particles is much higher (nearly twice) than that of the schemes of solution with the same salinity. When the salt sphere is added to RH, it flows into the down-snorkel after a short time period stay at the bottom of the vacuum chamber, and then stays at the bottom of the ladle until melting. During the melting period, the salt substance is slowly released, so that the mixing time at the bottom of ladle is longer. In the actual RH refining process, after adding heavy alloy that is difficult to melt, it is essential to pay attention to the mixing mechanisms of the substances at the bottom area of the ladle.